Development of a Specific Mini-Barcode From Plastome and its Application for Qualitative and Quantitative Identification of Processed Herbal Products Using DNA Metabarcoding Technique: A Case Study on Senna - Xiaolei Yu; Wei Tan; Han Gao; Lin Miao; Xiaoxuan Tian (Frontiers Media S.A., 2020)
Herbal products play an important role globally in the pharmaceutical and healthcare industries. However, some specific groups of herbal products are easily adulterated by confused materials on the market, which seriously reduces the products' quality. Universal conventional DNA barcodes would function poorly since the processed herbal products generally suffer from varying degrees of DNA degradation and DNA mixing during processing or manufacturing. For quality control purposes, an accurate and effective method should be provided for species identification of these herbal products. Here, we provided a strategy of developing the specific mini-barcode using Senna as an example, and by coupling with the metabarcoding technique, it realized the qualitative and quantitative identification of processed herbal products. The plastomes of Senna obtusifolia (L.) H.S.Irwin & Barneby and Senna occidentalis (L.) Link were newly assembled, and the hypervariable coding-regions were identified by comparing their genomes. Then, the specific mini-barcodes were developed based on the identified hypervariable regions. Finally, we applied the DNA metabarcoding technique to the developed mini-barcodes. Results showed that the lengths of plastomes of S. obtusifolia and S. occidentalis were 162,426 and 159,993 bp, respectively. Four hypervariable coding-regions ycf1, rpl23, petL, and matK were identified. Two specific mini-barcodes were successfully developed from matK, and the mini-barcode of primer 647F-847R was proved to be able to qualitatively and quantitatively identify these two processed Senna seeds. Overall, our study established a valuable way to develop the specific mini-barcode, which may provide a new idea for the quality control of processed herbal products.